Penerapan Model Pembelajaran Group Investigation Pada Hasil Belajar Mata Pelajaran IPA Siswa Kelas VII SMP Negeri 10 Kota Tangerang Selatan Tahun Pelajaran 2020/2021 (Universitas Pamulang, 2021)
ABSTRACTThe purpose of this paper is to find out the improvement of learning outcomes in science subjects for 7th grade students of SMP Negeri 10 Tangerang Selatan City through the application of the Group Investigation learning model. This research method is classroom action research. The subjects were 7th grade students of SMP Negeri 10 Tangerang Selatan City in science subjects. The number of students was 40, consisting of 18 male students and 22 female students. Data collection techniques are carried out through action planning activities, implementing actions, observing actions, and reflecting. The results of the study increased from 29.29% to 58.97%, 73.12% and to 85.07% at the second meeting of cycle II. Thus, it can be concluded that the application of the Group Investigation learning model can improve learning outcomes of science subjects for 7th grade students of SMP Negeri 10 Tangerang Selatan City.Keywords: learning outcomes; Group Investigation learning model; science subjects ABSTRAKTujuan dalam penulisan ini untuk mengetahui peningkatan hasil belajar mata pelajaran IPA siswa kelas 7.8 SMP Negeri 10 Kota Tangerang Selatan melalui penerapan model pembelajaran Group Investigation. Metode penelitian ini adalah penelitian tindakan kelas. Subyeknya siswa kelas 7.8 SMP Negeri 10 Kota Tangerang Selatan pada mata pelajaran IPA. Jumlah siswa sebanyak 40, terdiri dari 18 siswa laki-laki dan 22 siswa perempuan. Teknik pengumpulan data dilakukan melalui kegiatan perencanaan tindakan, pelaksanaan tindakan, pengamatan tindakan, dan refleksi. Hasil penelitian meningkat dari 29,29 % menjadi 58,97 %, 73,12 % dan menjadi 85,07 % pada pertemuan 2 siklus II. Dengan demikian dapat disimpulkan bahwa penerapan model pembelajaran Group Investigation dapat meningkatkan hasil belajar mata pelajaran IPA siswa kelas 7.8 SMPNegeri 10 Kota Tangerang Selatan.Kata kunci: Hasil belajar; model pembelajaran Group Investigation; mata pelajaran IPA.